Towards a sustainable development of the Gdańsk conurbation - opportunities and threats - PARTEKA, Tomasz (European Spatial Research and Policy, 1999)
The Gdańsk metropolitan area, made up of a closely interrelated group of cities: Gdańsk, Sopot and Gdynia, is undergoing a process of rapid transformation. The role and importance of the Gdańsk conurbation in the network of European cities depends on its following the sustainable development principles. The strategy of sustainable development (derived from a diagnosis and existing conditions) embraces three spheres of spatial development policy: - sustainable and polycentric urban system of the Gdańsk metropolitan area; - spatial and functionally balanced access to technical infrastructure; - active protection of the resources and assets of lhe natural and cultural environment. This strategy cąlls for the use of such instruments that will ensure permanent sustainability of development. Among these instruments Agenda 21 has the central role.